Chemical Composition and Anticancer Activity Of the Essential Oil Of Surian Heartwood - Rita K Sari; Wasrin Syafii; Suminar S Achmadi; Muhammad Hanafi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
Chemical constituents of the essential oil of water and steam distillates of surian heartwood (Toona sinensis) were analyzed by a gas chromatograph-mass spectrometer. Then, the oil was investigated in vitro anticancer bioassay for its possible antioxidant activity by DPPH free radical scavenging and antiproliferative effects by MTT method using Raji lymphoma cancer cell lines (ATCC CCL 86), HeLa cervical cancer cell lines (ATCC CCL2), and Vero normal cell lines (ATCC CCL 81). The essential oil yield from water and steam distillates of surian heartwood was 0.4% (w/w). Thirty-two compounds were identified, that consisted mainly of oxygenated sesquiterpenes (77%). The most representative compounds were spathulenol (21%), isospathulenol (7%), α-cadinol (7%), β-cedrenoxide (6%), and torreyol (5%). The oil showed less effective antioxidant, but the oil had high antiproliferative effects on Raji and HeLa cancer cells with IC50 28 and 134 μg ml-1, respectively when compared to Vero normal cells (IC50 1412 μg ml-1). Our findings suggest that the essential oil of surian heartwood might be considered as a potentially anticancer agent on human cancer cells, especially lymphoma cancer cells.Key words: antioxidant activity, antiproliferative effects, cancer cell lines, essential oil, Toona sinensis